2017
DOI: 10.1088/1361-6528/aa6951
|View full text |Cite
|
Sign up to set email alerts
|

Observation of variable hybridized-band gaps in Eu-intercalated graphene

Abstract: We report europium (Eu)-induced changes in the π-band of graphene (G) formed on the 6H-SiC(0001) surface by a combined study of photoemission measurements and density functional theory (DFT) calculations. Our photoemission data reveal that Eu intercalates upon annealing at 120 °C into the region between the graphene and the buffer layer (BL) to form a G/Eu/BL system, where a band gap of 0.29 eV opens at room temperature. This band gap is found to increase further to 0.48 eV upon cooling down to 60 K. Our DFT c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…We note that lower annealing temperatures has been reported in the Ref. [17] (120 C), confining the Eu diffusion between graphene and buffer layer, whereas annealing at 300 C shifts the Eu between the buffer and SiC and transforms the graphene to a bilayer. The annealing temperatures are higher in the current study resulting in a self-organized network of clusters of ∼25 atoms separated by at least 1.8 nm which behave independently in their magnetic response.…”
Section: Samples and Methodsmentioning
confidence: 60%
See 1 more Smart Citation
“…We note that lower annealing temperatures has been reported in the Ref. [17] (120 C), confining the Eu diffusion between graphene and buffer layer, whereas annealing at 300 C shifts the Eu between the buffer and SiC and transforms the graphene to a bilayer. The annealing temperatures are higher in the current study resulting in a self-organized network of clusters of ∼25 atoms separated by at least 1.8 nm which behave independently in their magnetic response.…”
Section: Samples and Methodsmentioning
confidence: 60%
“…Defect-free and epitaxial monoatomic layer of graphene has long been produced on SiC(0001) forming a continuous membrane over the whole surface including surface steps [9]. With these advances, modifying the electronic properties of graphene has been investigated either by depositing inert metals [10,11] and metaloxides [12] or by intercalating between the graphene and the metal substrate [13][14][15][16] or between graphene and the SiC buffer-layer [17]. Intercalation of metal donors or molecular acceptors into graphite is an old topic that culminated in recipes that enable control of the superstructures (staging phenomena), electrical conduction, superconductivity and even electrical energy storage in batteries (i.e., CF and CLi 6 ) [18].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the AFM structure was found to be better at opening a band gap in comparison to the FM structure. 132 Wei et al observed a strong interfacial exchange eld in a graphene/ EuS heterostructure as a consequence of strong Zeeman splitting. 133…”
Section: Effect Of Heavy Elements On 2d Carbon Magnetismmentioning
confidence: 99%
“…Intercalation of Eu between Ir substrate and graphene (prepared by CVD) reveals that the structure and magnetic properties of the intercalated Eu depend on the coverage which does not seem to affect the graphene electronic structure [6]. However, a recent study shows that Eu intercalation between graphene and the SiC buffer layer modifies the π−band of graphene significantly [9].…”
Section: Introductionmentioning
confidence: 99%
“…Metal intercalation under graphene on various substrates is by now common practice [1,2,3,4,5,6,7,8,9,10,11]. Indeed, it has been demonstrated that rare earth metals (RE = Nd, Sm, Dy, Er and Yb, and Eu, for example) deposited on graphene grown on SiC or Ir substrate can intercalate under the graphene lattice by annealing pre-deposited metals at elevated temperatures [1,4,9,12]. Adsorbed metals on graphene have also been used to take advantage of special growth or to mutually modify the electronic properties of graphene and the adsorbed metal atoms on it.…”
Section: Introductionmentioning
confidence: 99%